2016
DOI: 10.1111/tmi.12689
|View full text |Cite
|
Sign up to set email alerts
|

Sickle cell disease in western Sudan: genetic epidemiology and predictors of knowledge attitude and practices

Abstract: Summaryobjective To investigate the epidemiology of sickle cell disease (SCD) and determinants of knowledge, attitudes and practices (KAP) towards SCD in western Kordofan State, Sudan.methods A community-based, descriptive, cross-sectional study was conducted in three towns. Three hundred and seventy-two households were polled, and blood samples for haemoglobin phenotyping were collected from 1116 individuals. Sociodemographic, socio-economic and KAP data were collected using investigator-administered question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
31
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 34 publications
(45 reference statements)
5
31
3
Order By: Relevance
“…This limitation should not affect our study, because (1) the AI haplotype has only been found in tribes in India and in population of the eastern part of Saudi Arabia, and most of our patients originate from Western and Central Africa. In addition, none of the published studies in SCD patients from Eastern Africa have reported the presence of the AI haplotype [51][52][53][54] ; and (2) the SEN and the AI haplotypes share the rs 7482144 C/T, which is the strongest predictor of HbF expression, and is located on chromosome 11, even in the AI group [55][56][57] In our study, G6PD deficiency was not defined by gene analysis but by abnormally low G6PD activity. As G6PD deficiency is caused by mutations in the X-linked G6PD gene, heterozygous females may have normal G6PD activity or be deficient.…”
Section: Discussioncontrasting
confidence: 61%
“…This limitation should not affect our study, because (1) the AI haplotype has only been found in tribes in India and in population of the eastern part of Saudi Arabia, and most of our patients originate from Western and Central Africa. In addition, none of the published studies in SCD patients from Eastern Africa have reported the presence of the AI haplotype [51][52][53][54] ; and (2) the SEN and the AI haplotypes share the rs 7482144 C/T, which is the strongest predictor of HbF expression, and is located on chromosome 11, even in the AI group [55][56][57] In our study, G6PD deficiency was not defined by gene analysis but by abnormally low G6PD activity. As G6PD deficiency is caused by mutations in the X-linked G6PD gene, heterozygous females may have normal G6PD activity or be deficient.…”
Section: Discussioncontrasting
confidence: 61%
“…(Table 4 ) shows severity score grading of SCA group. 4 12.5 N:number of SCA patients; % percentage among SCA group There is no correlation observed between the severity score and renal parameters in this study, but there is positive correlation between PCR, age and systolic BP. (Table 5) shows the correlation between renal parameters, age, BP and severity score.…”
Section: Results: Characteristics Of Study Populationmentioning
confidence: 65%
“…Sudan is located in east Africa, a region known for a high genetic diversity among its population (Hollfelder et al, 2017). The genetic make-up of the Sudanese population is under opposing homogenizing, consanguinity rate > 60% in some regions, and diversifying powers, admixture and migration including migration to and from the Middle East (Daak et al, 2016;Hollfelder et al, 2017).…”
Section: Discussionmentioning
confidence: 99%